2021
DOI: 10.1007/s11427-020-1910-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques

Abstract: In multicellular and even single-celled organisms, individual components are interconnected at multiscale levels to produce enormously complex biological networks that help these systems maintain homeostasis for development and environmental adaptation. Systems biology studies initially adopted network analysis to explore how relationships between individual components give rise to complex biological processes. Network analysis has been applied to dissect the complex connectivity of mammalian brains across dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 329 publications
(411 reference statements)
0
5
0
Order By: Relevance
“…Lipid transport is one of the functions of a membrane contact site (MCS), which provides a fast and nonvesicular way for material exchange. MCSs have a functional proteomic and/or lipidomic composition which is required for maintenance and function of the architecture ( 19 , 20 ). In mammalian cells, the ER-localized proteins VAMP-associated protein (VAP) A and B have been shown to establish MCSs with multiple organelles including the Golgi, endosomes, and peroxisomes ( 21 ).…”
mentioning
confidence: 99%
“…Lipid transport is one of the functions of a membrane contact site (MCS), which provides a fast and nonvesicular way for material exchange. MCSs have a functional proteomic and/or lipidomic composition which is required for maintenance and function of the architecture ( 19 , 20 ). In mammalian cells, the ER-localized proteins VAMP-associated protein (VAP) A and B have been shown to establish MCSs with multiple organelles including the Golgi, endosomes, and peroxisomes ( 21 ).…”
mentioning
confidence: 99%
“…Due to its close ties to the PM and CW, the cytoskeleton can also take part in the dynamics of CW-involved responses to biotic and abiotic stress [ 80 ]. Targeting of the PM-CW-localized defensive regulator (cellulose or callose) to the plasma membrane also requires the cytoskeleton.…”
Section: The Cytoskeleton Regulates Endo-membrane Trafficking Of Prrs...mentioning
confidence: 99%
“…(6) As a complex dynamic filamentous network throughout the whole cell, it would be interesting to reveal the real-time dynamic changes in the cytoskeleton and the ultrastructural characterization of pathogen and host responses during the interaction. The recent application of high-spatiotemporal-resolution imaging techniques and volume imaging systems [ 114 , 115 , 116 ] will help us better understand the cytoskeleton remodeling and function during the plant defense response. Recently, Vernet et al successfully observed the nematode–root interactions in tomato using light sheet fluorescence microscopy (LSFM) and optical projection tomography (OPT) [ 117 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%